Preserving Local Traditions in the Digital Age: Adapting the 'Mapak Tanggal' Ritual as an Intergenerational Solution - Gunagraha, Shindid; Kholilurrahman, Kholilurrahman (JURNAL ISLAM NUSANTARA, 2024)
This research focuses on the preservation of the "Mapak Tanggal" tradition in Mojo Village, East Java, amidst the challenges of the digital era. This tradition is an annual religious ritual that has an important role in strengthening social cohesion and maintaining the community's cultural identity. However, modernization and digitalization bring significant changes in participation patterns, especially among the younger generation who are more interested in technology than physical-based traditions. This research uses a qualitative approach with a case study design. Data were collected through in-depth interviews, direct observation, and documentation, involving religious leaders, community leaders, and cross-generational communities as key informants. Data analysis was conducted through a process of data reduction, data display, and verification to ensure the validity of the findings. The results showed that although digitalization affected the younger generation's participation in the tradition, the Mojo Village community successfully integrated technology as a preservation tool. Social media is used to document and promote the tradition of "Mapak Tanggal," thus attracting the interest of the younger generation and expanding audience reach. Religious leaders play an important role in maintaining a balance between cultural values and religious teachings through a moderate, inclusive approach. The findings suggest that technological adaptation can support the sustainability of local traditions without compromising their cultural and spiritual essence. The implications of this research emphasize the importance of an adaptive approach in the preservation of local traditions in the digital era.